Factors Affecting The Selection of Fair Value Methods for Investment Property - Setijaningsih, Herlin Tundjung; Handoyo, Sarwo Edy; Sundari, Novia (Jurnal Organisasi dan Manajemen, 2021)
The purpose of this study is to analyze the effect of leverage, profitability, information asymmetry, and the gain on the fair value difference on the selection of the fair value method for investment property by PSAK 13. The population of this study is all companies listed on the Indonesia Stock Exchange for the period 2016-2018. The sample selected by purposive sampling amounted to 53 companies. The data processing technique uses the STATA 14.2 program. Logistic regression is used to analyze the hypothesis. Findings. The results of this study indicate that leverage, profitability, and information asymmetry do not affect the selection of the fair value method for an investment property. However, the gain on fair value difference negatively affects the choice of the fair value method for an investment property.